2017
DOI: 10.1101/190421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influential parameters for the analysis of intracellular parasite metabolomics

Abstract: 20 Due to improved instrument sensitivity and access, the use of metabolomics is gaining 21 traction for the study of many organisms and pathogens. were most appropriate for normalization as they separate sample groups and reduce 32 noise within the data set. However, these post-analysis steps did not remove the 33 contribution from the host erythrocyte, in the form of membrane rich 'ghosts', and levels 34 of technical sample variation persisted. In fact, we found that host contamination is as 35 influen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Other 'omics-level methods also suffer from difficulty identifying parasite signal over human host material. An abundance of host proteins and metabolites leads to difficulty, even in vitro, in generating high-quality proteomics [74] and metabolomics [75], respectively. Thus, proteomics and metabolomics on samples directly from hosts have focused on analyzing human serum to infer biology of disease diversity and drug resistance effects through host-parasite interactions [76][77][78][79][80][81].…”
Section: Direct-from-host Methodologies Exhibit Distinct Challenges Amentioning
confidence: 99%
“…Other 'omics-level methods also suffer from difficulty identifying parasite signal over human host material. An abundance of host proteins and metabolites leads to difficulty, even in vitro, in generating high-quality proteomics [74] and metabolomics [75], respectively. Thus, proteomics and metabolomics on samples directly from hosts have focused on analyzing human serum to infer biology of disease diversity and drug resistance effects through host-parasite interactions [76][77][78][79][80][81].…”
Section: Direct-from-host Methodologies Exhibit Distinct Challenges Amentioning
confidence: 99%
“…The extraction methods and mass spectrometry platforms used in previous studies precluded them from detecting a large number of lipid metabolites [4,8]. Several recent studies [6,23,24] quantified more metabolites than in the studies by Babbitt et al [8] or Olszewski et al [4]. However, they either did not examine all parasite stages or did not include matched uninfected erythrocyte cultures during the IDC (see Table 1).…”
Section: Metabolomics Of Blood-stage Malaria Parasitesmentioning
confidence: 99%
“…29 In a recent study on the use of purified in vitro-grown ringstage intraerythrocytic Plasmodium falciparum parasites in untargeted metabolomics studies, the authors investigated confounding factors that influence data interpretation, including host contamination and normalization approaches (including double-stranded DNA, total protein, and parasite numbers), and revealed that normalization does not remove the contribution from the parasite's extracellular environment (culture media and host erythrocyte). 30 While analyzing the cell-secretome (i.e. metabolites secreted into the media), cell count-or culture volume-based normalization can be challenging.…”
Section: Cell-based Methodsmentioning
confidence: 99%